Uterine artery Doppler and sFlt‐1/PlGF ratio: prognostic value in early‐onset pre‐eclampsia. (27th March 2014) - Gómez‐Arriaga, P. I.; Herraiz, I.; López‐Jiménez, E. A.; Escribano, D.; Denk, B.; Galindo, A.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 488–489